2021
DOI: 10.1111/ijcp.14919
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and in‐hospital mortality of patients with COVID‐19 in Chile: A prospective cohort study

Abstract: Aims of this study To describe the Latin American population affected by COVID‐19, and to determine relevant risk factors for in‐hospital mortality. Methods We prospectively registered relevant clinical, laboratory, and radiological data of adult patients with COVID‐19, admitted within the first 100 days of the pandemic from a single teaching hospital in Santiago, Chile. The primary outcome was in‐hospital mortality. Secondary outcomes included the need for respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
3
0
0
Order By: Relevance
“…The overall in-hospital mortality rate detected in our series of COVID-19 patients was higher than that observed in previous studies which included younger patients ( 16 , 17 ) and similar to that observed in other studies which enrolled geriatric patients with several comorbid conditions ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 88%
“…The overall in-hospital mortality rate detected in our series of COVID-19 patients was higher than that observed in previous studies which included younger patients ( 16 , 17 ) and similar to that observed in other studies which enrolled geriatric patients with several comorbid conditions ( 18 , 19 ).…”
Section: Discussionsupporting
confidence: 88%
“…However, no signi cant differences were observed upon calculation of the Charlson Comorbidity Index for each group. The most prevalent symptoms and signs, including dyspnea, fever, dry cough, tachypnea, and decreased oxygen saturation, were consistent with previous studies [39][40][41][42][43][44][45][46][47][48][49][50]. Unvaccinated patients had a higher prevalence of dyspnea, increased respiratory rate, and lower oxygen saturation values, corroborating ndings from similar studies [51][52][53][54][55].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, in the second year of observation, the percent of in-hospital mortality remained at a high level, close to 20% which was typical for the colder months of the previous year. It was confirmed that the in-hospital mortality rate observed in Silesian voivodeship was higher than the values reported by other authors [ 19 , 20 ]. It is worth mentioning that the development of population immunity is a long-term process.…”
Section: Discussionsupporting
confidence: 84%